PARTISIPASI MASYARAKAT DALAM PENYUSUNAN RPJM-Des DESA KEDUNGBANTENG KECAMATAN TANGGULANGIN KABUPATEN SIDOARJO - Sa'diyah, Halimatus (Inovasi Pembangunan : Jurnal Kelitbangan, 2024)
Abstract: This research aims to identify the level of community participation and involvement in the preparation of the Village Medium Term Development Plan (RPJM-Des) document in Kedungbanteng Village, Tanggulangin District, Sidoarjo Regency. In this research, qualitative methods were used, and informants were selected using a purposive sampling method. Data was obtained through three data collection techniques, namely observation, interviews and documentation. Primary data was collected from observations and interviews with relevant respondents, while secondary data came from literature studies which included books, articles, scientific journals and documents related to the Village Medium Term Development Plan (RPJM-Des). The results of research on community participation or involvement in the preparation of the Village Medium Term Development Plan (RPJM-Des) document in Kedungbanteng Village, Tanggulangin District, Sidoarjo Regency show that; First, the participation indicators in the planning stage are still not optimal, where from several meetings held by the Kedungbanteng village government, less than 50% of the community's attendance rate. Second, the participation indicators in the implementation stages are quite optimal, both in the implementation of physical and non-physical development carried out in Kedungbanteng village. Third, the indicators of participation in the utilization stage are also quite optimal, because many people in Kedungbanteng village have been helped by the programs and development carried out by the village, both physical and non-physical development.